(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Objective: To evaluate the challenges, strategies, and outcomes involved in establishing and running a Bone Marrow Transplant (BMT) program in a resource-constrained rural area, with a focus on infrastructure development, human resource capacity building, and collaborative efforts for sustainable success Study design: A Descriptive cross-sectional observational study. Study Place & Duration: Gambat Institute of Medical Sciences (GIMS) from Jan 2021 to March 2021 Methods: A large size public sector facility was established in remote area of interior Sindh province of Pakistan. The program involved construction of infrastructure, human resource development, and setting up of building maintenance protocols. The essential steps involved in its establishment were human resource capacity building and teamwork. Results and Conclusion: Establishing and successful BMT program in the public sector in resource-limited setting is a difficult task that needs a vibrant administrative support, involvement of experienced person to lead the facility and twining with some advanced center for initial human resource development. Resource constraintsnations may have a somewhat higher incidence of complications due to socioeconomic variables and increased infection risks. While transplantation has the ability to satisfy unmet medical needs, future collaborations headed by experienced transplantation facilities will be required for the development and extension of BMT in the poor countries.